High consequence systems phenomenological characterization: A tutorial1. Issue 4 (18th April 2013) - Sanders, Gary A.; Sarkani, Shahram; Mazzuchi, Thomas
Abstract Effective and efficient risk management processes include the use of modeling and simulation during the concept exploration phase as part of the technology and risk assessment activities, with testing and evaluation tasks occurring in later design development phases. However, some safety requirements and design architectures may be dominated by the low probability/high consequence, previously unknown or uncharacterized vulnerabilities that require very early testing to characterize and efficiently mitigate. Failure to address these unique risks has led to catastrophic systems failures including the Space Shuttle Challenger, Deepwater Horizon, the Fukushima nuclear reactor, and Katrina levee failures. Discovering and addressing these risks later in the design and development process can be very costly or even lead to project cancellation. This paper presents a framework for the risk management process adoption of early hazard phenomenology testing to inform the technical risk assessment, requirements definition, and conceptual design. A case study of the lightning design vulnerability of the insensitive high explosives being used in construction, demolition, and defense industries will be presented to examine the impact of this vulnerability testing during the concept exploration phase of the design effort. ©2013 Wiley Periodicals, Inc. Syst Eng 16: